TRADE PERFORMANCE OF EXPORT OF INDIAN AGRICULTURAL PRODUCTS - Rama Rani, Dr. Rashi Mittal (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The recognition of India has always remained as a agro-based country and on the other hand till 2011 all the allied activities of agriculture have contributed around 17% to the GDP of the country. Till the recent past i.e. in 2018-19 total agriculture export has reached to a new height of USD 34 billion. But still there are certain fluctuation in the CAGR of total exports and agro-based exports. There are a number of reasons for the same i.e. from policy reforms to domestic consumption. This present study will evaluate the reasons of these fluctuation and try to present a clear view of growth related to Agro-exports and relation of the same to total exports. The researcher has considered a period of around 10 years for analysis i.e. 2010-2019, secondary data is used in the study and Correlation is used as a model of analysis.